Local Anaesthesia in Dentistry. - Baart, J. A. (Jacobus Andries), 1950- (John Wiley & Sons, 2009)
Local Anaesthesia in Dentistry is a practical guide for both students and general practitioners to this essential area of clinical practice. Highly illustrated in full colour throughout, the book provides clear and practical guidance to the administration of local anaesthesia. The book introduces the reader to the concept of nerve conduction and pain as well as providing an explanation of the anatomy of the trigeminal nerve. Further chapters cover such key areas of practice as regional anaesthesia, local anaesthesia in children, pharmacology, local and systemic complications, general practical.